Prescription of physical exercise and cognitive activities for subjects with autism spectrum disorder: A scoping review of the main methods (Research, Society and Development, 2022)
Introduction: Children with Autistic Spectrum Disorder exhibit an extreme difficulty on the control and motor development once it is affected considerably to the point of harming in the activities of daily life. Objective: The research aimed to verify which motor and cognitive activities are more used in interventions aimed at children with autistic spectrum disorder, as well as the main limitations reported by authors in the identification of these activities. Methodology: The present study is a literature scope review. The choice of articles was conducted by defining a search string that was standardized for all databases. The databases used were ACM Digital Library, ScienceDirect, Google Academic, PePSIC-BVS, Web of Science, Scopus, National Library of Medicine and Taylor & Francis Online. Articles published January 2010 and December 2021 were included. Results: The main motor and cognitive activities reported in the scientific literature were: running, walking, aquatic activities, martial arts and dance. In addition, trampoline training was pointed out as an alternative to work bilateral coordination. Conclusion: Individual aerobic activities or collective activities are used more frequently in the analyzed studies. Thus, it was pointed out that such activities are suitable for working on motor and cognitive development in children with autism spectrum disorder, however, it is necessary to take into account the degree of autism and psychosocial particularities of the subjects.